Media Relations Strategy of Seqara Communications in Maintaining Oppo's Image - andie wibianto; Aminah Swarnawati (ULTIMA Comm, 2025)
Media relations remains a cornerstone service offered by public relations firms to safeguard a product's reputation within the realm of marketing communications. This study aims to analyze Seqara Communications' media relations strategy to maintain Oppo's brand image. The research methodology utilizes a qualitative, phenomenological approach, which seeks to understand a social phenomenon by gathering in-depth data about individuals' experiences, including their motivations, attitudes, beliefs, and behaviors. Seqara Communications' media relations strategy for Oppo involved a multi-step process. This included: target media research; identification and mitigation of potential issues; development of compelling stories and media spokespersons; cultivation of relationships with editors and key journalists aligned with their reporting agendas; provision of tailored media kits to priority journalists; follow-up with journalists to facilitate news coverage or understand why content was not published; and ongoing monitoring of media reports and evaluations.